Urgensi Kompetensi Profesional Bagi Calon Konselor Islam - Syaputra, Yogi Damai; Monalisa, Monalisa; Monika, Ika; Cantika, Grasi; Halida, Halida; Syawaluddin, Syawaluddin (Universitas Islam Negeri Madura, 2024)
Professional competency is the basic foundation for prospective counselors. This research aims to examine the urgency of professional competence for prospective counselors. The data source in this library study research was obtained from research articles found on google scholar in the period 2018 - 2023. Data was obtained through Harzing's publish or perish application. By using the keywords professional competence of counselors and professional competence of prospective counselors, 400 articles related to these keywords were obtained. Based on the sorting of data analysis, 13 articles were relevant to the objectives of this research. The research results show that seven aspects of competency must be mastered, including 1) being able to carry out assessment activities; 2) mastering the theory of counseling well and being able to implement it; 3) able to develop guidance and counseling programs; 4) able to implement the designed guidance and counseling program; 5) master the process assessment instruments and counseling results assessment; 6) Understand and be able to maintain professional ethics; 7) able to carry out research in developing the science of guidance and counseling. These results are important for prospective counselors to improve their professional competence so they can compete with current global challenges. This research recommends that future researchers provide interventions to prospective counselors to improve professional competence.